Scopes of community participation in development for adaptation: Experiences from the Haor region of Bangladesh. (December 2020) - Chowdhooree, Imon; Dawes, Les; Sloan, Mellini
Abstract: In the disaster-context, adaptation is considered as the process of changing status with effective strategies for reducing disaster risks and enhancing resilience. Planning approaches for adaptation often merges with socio-economic development, applying a top-down, technocratic rational paradigm. Whereas the bottom-up process of planning encourages communities to participate for sharing the power of decision making, incorporating its knowledge, ideas, and concerns. Particularly in developing countries, non-governmental organization (NGO)s, collaborating with communities and governmental organizations, conduct community development projects. The community reactions towards these projects and condition of community participation in their planning process are needed to be evaluated to develop a better understanding about the scope of community participation in the local level development activities for reducing future risks. This case study based research, employing qualitative tools, studies two settlements in the Haor region of Bangladesh to investigate NGO-driven development projects and their planning process through the lens of community participation. The region is a vast tectonic depression where its inhabitants live with significant seasonal flood risks, accommodating themselves on constructed islands. The empirical evidences are evaluated to identify levels of community participation and it has been found as ritualistic in most of the cases, where the community concerns and demands are ignored through convincing them, manipulating their ideas and providing therapies. It also does not often allow to empower the community to take control over the project, which is considered as necessary in a disaster context to coincide adaptation with development, aiming to enhance community resilience.